Prodendronic polyamines from stable or labile methacrylates obtained by selective Michael addition onto asymmetric diacrylic compounds. Issue 16 (20th May 2014) - Redondo, Juan Alfonso; Navarro, Rodrigo; Martínez‐Campos, Enrique; Pérez‐Perrino, Mónica; París, Rodrigo; López‐Lacomba, José Luis; Elvira, Carlos; Reinecke, Helmut; Gallardo, Alberto
ABSTRACT A new synthetic strategy for the preparation of methacrylic monomers and polymers carrying acyl β‐amino groups is presented. The approach is based on the Michael addition of aliphatic amines onto asymmetric acrylic/methacrylic compounds, reacting the amine highly selectively with the acrylic unit while leaving the methacrylic moiety unreacted. The corresponding polymers are then obtained by conventional radical polymerization. The use of N, N, N′, N′‐tetraethyldiethylenetriamine (TEDETA) as the secondary amine leads to TEDETA moieties supported on polymeric chains. The new aminopolymers are sensitive to pH and to temperature exhibiting a lower critical solution temperature of between 50 and 90 °C. A further interesting feature of the new approach is that the stability toward hydrolysis of the side β‐amino acyl compounds was found to be dependent on whether an acrylamide or an acrylate is employed as the acrylic group of the asymmetric starting material. The esters exhibit an enhanced sensitivity to hydrolysis, compared to standard aliphatic esters, and decompose releasing a derivative of the amine precursor, within hours or weeks, depending on the pH and temperature conditions. The use of the amides leads to stable polymers when the same experimental conditions are applied. The novel dendronic polyamines have been proven to interact with DNA and to transfect cells with efficiency close to that obtained with polyethyleneimine vectors used as positive controls. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2297–2305